Keterampilan Pedagogik dan Minat Mengajar sebagai Prediktor Kesiapan Mengajar Calon Guru - Abelia Paramista; Riza Yonisa Kurniawan (Advances In Education Journal, 2026)
This study examines the effect of teaching skills and teaching interest on teaching readiness among students of the Economic Education Program, Universitas Negeri Surabaya, class of 2022. The main problem addressed is the variation in students’ readiness to teach despite having undertaken pedagogical courses. This research aims to analyze the partial and simultaneous influence of teaching skills and teaching interest on teaching readiness. A quantitative explanatory approach was employed. Data were collected using structured questionnaires distributed to 30 students selected through simple random sampling. The data were analyzed using multiple linear regression with classical assumption tests. The results indicate that teaching skills have a positive and significant effect on teaching readiness, while teaching interest does not show a significant partial effect. However, teaching skills and teaching interest simultaneously have a significant influence on teaching readiness, with a determination coefficient of 35.9%. These findings suggest that teaching readiness is primarily shaped by pedagogical competence supported by internal motivation. The study concludes that strengthening practical teaching skills and fostering professional interest are essential to prepare competent future teachers.